2018
DOI: 10.1016/j.compstruct.2017.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of assembly stress in composite structures using the deep-hole drilling technique

Abstract: The deep-hole drilling (DHD) method is a residual stress measurement method that is widely used for measurements in thick metallic components. In the DHD method a reference hole is first drilled through the thickness of the component. The diameter of the hole is measured accurately and then a cylindrical core of material around the hole is trepanned from the component, relaxing the residual stresses in the core. Finally, the diameter of the reference hole is re-measured and the change in diameter used to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…There has been a huge breadth of research that has been undertaken in the numerical modeling of the manufacturing process of fiber reinforced laminates, as Baran et al [3] showed. It is clear that much progress has been made over the past few decades and it is now possible to accurately predict many physical phenomena accurately by choosing and correctly implementing one of the [11,[13][14][15][16] Hole-drilling [19,27] [20] -Potentially global scale if laminate is thin -Bixal stress distribution -Accuracy decreases with depth of cut [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Ring-core [40][41][42] Note: ?, there is potential but it has not been done to date; , it is possible with some caveats. many models and techniques available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a huge breadth of research that has been undertaken in the numerical modeling of the manufacturing process of fiber reinforced laminates, as Baran et al [3] showed. It is clear that much progress has been made over the past few decades and it is now possible to accurately predict many physical phenomena accurately by choosing and correctly implementing one of the [11,[13][14][15][16] Hole-drilling [19,27] [20] -Potentially global scale if laminate is thin -Bixal stress distribution -Accuracy decreases with depth of cut [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Ring-core [40][41][42] Note: ?, there is potential but it has not been done to date; , it is possible with some caveats. many models and techniques available.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Garza et al [ 28 ] have shown that DHD is not able to accurately capture cure induced residual stress unless the thickness of stacks of similarly orientated plies is larger than the hole size being used. Therefore, for most cross‐plied laminates it is not possible to use the DHD technique to measure cure induced residual stress.…”
Section: Destructive Methodsmentioning
confidence: 99%
“…The residual stresses were analyzed experimentally for FRPCs by using different techniques such as the layer removal method [16], the hole drilling method [17,18], deep hole drilling technique [19,20], the contour method [21], the first ply failure method [22], the radial cutting method [23] and the matrix removal methods [24]. These techniques have been employed mainly to measure the in-plane residual stresses in continuous FRPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Residual stress evaluation methods can be destructive, semidestructive, or nondestructive [4]. The main destructive and semidestructive techniques include contour, sectioning, hole-drilling, ring-core, and deep-hole methods [5][6][7][8][9], among others. However, these methods are complicated, time-consuming, and will cause damage to the material.…”
Section: Introductionmentioning
confidence: 99%
“…MHz and transducer diameters of 6 mm, 8 mm, and 10 mm, respectively. The beam divergence angle of each sample was calculated according to Equation(9), and the respective results were 27.waveform shown inFigure 5cwas clearly observed and possessed a clear outline. Therefore, for the 2.5 MHz transducer, the optimum diameter was 10 mm.…”
mentioning
confidence: 99%